University and community: A plan for communication - SHANA, ZUHRIEH; LAHIANI, HANENE; ALWAELY, SUAD; ALSHALABI, NAHLA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study highlights the importance of cultural interactions between university and community through understanding the modern university’s role in servicing its community. The study also confronts the challenges that universities face in creating cooperative partnerships with their communities. The university community activities at AlAin University have been tracked for five academic semesters to predict their pattern of development. It supports the data generated from a Likert-scale questionnaire with two open ended questions. The questionnaire explores the extent of faculty involvement with community via teaching, research and service. Results have been analyzed, then activities to improve this collaboration culture are recommended.